Knowledge of HIV as an Important Rural Problem: A Descriptive Study of Priority Health Problems - Kurniawan, Nanang; Apriyanti, Dewi; Ratnawati, A. Sri; Zahrany, Asyifa; Haris, Yuli Fathiyah; Palutturi, Sukri; Rachmat, Muhammad (Jurnal Ilmiah Kesehatan (JIKA), 2024)
Health as a complex problems requires prioritisation and identification of root causes to determine appropriate interventions. This study aimed to determine the priority health problems in Bonto Matene Village, Segeri District, Pangkajene and Islands Regency. Perform research using descriptive approaches. Univariate analysis was applied to determine the hierarchy of health concerns based on survey responses collected through standardized questionnaires conducted during interviews. The prioritization of health problems was carried out by utilizing Hanlon's qualitative method through focus group discussions. The Ishikawa diagram, also referred to as the fishbone diagram, was used to identify the root cause of a problem. The survey, which included 272 families and a total of 520 individuals, identified 14 health problems. The factors contributing to these issues encompass substandard waste management practices resulting in improper composting, occupational health disorders, occupational accidents, hypertension, insufficient COVID-19 vaccination doses (3), segregation of organic and non-organic waste, work-related injuries, ISPA (Influenza-like Illness), limited access to clean water, inadequate hand hygiene practices, smoking within the household, insufficient physical exercise, limited knowledge about HIV, and irregular consumption of TB medication. The primary health issue in Bonto Matene Village was a lack of knowledge about HIV. To address this, an intervention is developed to enhance HIV knowledge through direct education and various media platforms. The aim is to raise awareness and improve community understanding of HIV, while also promoting the adoption of safe and healthy behaviors in place of risky behaviors.